A Method For Generating Plane Wave And Zero-Offet Vsp Synthetic Seismograms - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 1985)
Synthetic Vertical Seismic Profiles (VSP) seianograms are a useful aid to the interpretation of VSP re- conds, Plane wave VSP syntherics multiples and mode conversions can be computed rapldly n the frequency domain using a new recursive formulation. The method urilises the concept of